2015
DOI: 10.1007/s00784-015-1608-z
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of intrabony defects with guided tissue regeneration in aggressive periodontitis: clinical outcomes at 6 and 12 months

Abstract: Both periodontal regeneration and conventional periodontal surgery are effective treatments for AgP patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
36
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(38 citation statements)
references
References 45 publications
2
36
0
Order By: Relevance
“…In Queiroz et al's study, the use of a nonresorbable barrier resulted in similar changes to those obtained in patients in which the bone substitute was mixed with P-15 without any membrane [33]. In Rakmanee et al's research, both clinical and radiographic results showed substantial comparability between GTR procedures and access flap therapies [27,34]. To the best of our knowledge, the concept of using MPM in patients with AgP has not been tested yet.…”
Section: Discussionmentioning
confidence: 82%
“…In Queiroz et al's study, the use of a nonresorbable barrier resulted in similar changes to those obtained in patients in which the bone substitute was mixed with P-15 without any membrane [33]. In Rakmanee et al's research, both clinical and radiographic results showed substantial comparability between GTR procedures and access flap therapies [27,34]. To the best of our knowledge, the concept of using MPM in patients with AgP has not been tested yet.…”
Section: Discussionmentioning
confidence: 82%
“…In non‐randomized, comparative studies, the reported outcomes did not show a significant advantage of one surgical approach over another; the differences between groups were not significantly different. In both included RCT, no significant advantage of guided tissue regeneration procedures over EMD and simplified papilla preservation flap (SPPF) approaches could be found …”
Section: Resultsmentioning
confidence: 96%
“…Apparently, none of the biomaterials used in the included studies could be related to better outcomes if compared to other biomaterials. Considering only the RCT, none of the biomaterials were found to be more beneficial than others . Interestingly, in Queiroz et al.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Despite the careful minimally invasive surgeries, in which a simplified papilla preservation flap was used, interproximal wound dehiscence with membrane exposure occurred in the majority of the regenerative surgical treatment. 15 Regenerative surgery of interproximal intrabony defect is very difficult to perform, particularly in esthetics sensitive areas.…”
Section: Discussionmentioning
confidence: 99%